Fixed Assets: Problems of Reliable Reflection in the Reporting of Industrial Enterprises - MOSHCHENKO, Oksana V.; ROKOTYANSKAYA, Violetta V.; BAYZULAEV, Salih A.; NEPEEVA, Halimat U.; KUVALDINA, Irina S. (Journal of Advanced Research in Law and Economics, 2018)
The concept of fixed assets is revealed in this article. The analysis of the depreciation degree of the fixed assets was carried out using the economic activity types in the period from 2011 to 2015. The existence and structure of fixed assets of commercial and non-commercial organizations using kinds of economic activity in 2015 are considered. The coefficients of renewal and retirement of fixed assets in bodies by means of the economic activity types are analyzed. Eight groups of typical mistakes are distinguished which accountants of industrial enterprises when accounting for fixed assets make and described in details. The emphasized problems are classified regarding audit criteria for the financial statements on a regular reflection of the condition and movement of fixed assets in the enterprise's business reports. A program of their internal control has been developed as a single possible solution of distortions in accounting indicators for fixed assets. The article also examines the valuation and revaluation of fixed assets in accounting. The main mistakes, violations, and facts of fraud are disclosed which made in the conduct of both assessment and reassessment of fixed assets, affecting the reliability of the indicators of financial statements. The analysis of additional signs of the fixed assets state is given characterizing the legality of revaluation of this type of assets.